KEMAMPUAN MENULIS SURAT PERMOHONAN IZIN DI SMP NEGERI 3 CAPKALA KABUPATEN BENGKAYANG - Desilianti Desilianti; Sesilia Seli; Deden Ramdani (Universitas Tanjungpura, 2019)
AbstractThis research on the ability of students to write permission letters. The problem in this research is students often underestimate the application for permission request letter, so the teacher thinks students who are not attending school are considered negligent. This is very influential on student absenteeism presence.The method in this research used a descriptive method. Form of research is qualitative. The source of the data was VII grade students of SMP Negeri 3 Capkala Kabupaten Bengkayang consisting of 39 students in the academic year 2018/2019. The data in this study were using spelling, standard word, effective sentences, preparing paragraphs and placing the parts of the application for permission request letter written. Data collection techniques used direct techniques and indirect techniques. Data collection tool in this study used a test of an essay.The results of this study, the average value using thespelling 60. The average value using the word 86,25. The average value using the sentence 41,68. the average value compiling paragraphs 41,98. The average value places the lincense part 92,70. The ability of students to write permission in SMPN 3 Capkala Kabupaten Bengkayang district 2018/2019 academic year the average value of 66,291 category C. Keyword: Writing Skill, Perimission Requests Letter